2019
DOI: 10.1038/s41522-019-0102-9
|View full text |Cite
|
Sign up to set email alerts
|

Blue laser light inhibits biofilm formation in vitro and in vivo by inducing oxidative stress

Abstract: Resolution of bacterial infections is often hampered by both resistance to conventional antibiotic therapy and hiding of bacterial cells inside biofilms, warranting the development of innovative therapeutic strategies. Here, we report the efficacy of blue laser light in eradicating Pseudomonas aeruginosa cells, grown in planktonic state, agar plates and mature biofilms, both in vitro and in vivo, with minimal toxicity to mammalian cells and tissues. Results obtained using knock-out mutants point to oxidative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 35 publications
(50 reference statements)
5
35
0
1
Order By: Relevance
“…Concentrations of 50 and 100 nM CUR‐SPM were employed, alongside with increasing concentrations of free CUR (5 μM, 10 μM, 20 μM, 50 μM, 100 μM, 200 μM). For every condition, the wells were irradiated with three sublethal blue laser protocols (L1, L2 and L3 as described in Table 1), based on our previous experience with antimicrobial blue laser irradiation [16]. Bacterial growth after 24 hours was evaluated by measuring the OD 600 and compared with nontreated bacteria (CTRL).…”
Section: Methodsmentioning
confidence: 99%
“…Concentrations of 50 and 100 nM CUR‐SPM were employed, alongside with increasing concentrations of free CUR (5 μM, 10 μM, 20 μM, 50 μM, 100 μM, 200 μM). For every condition, the wells were irradiated with three sublethal blue laser protocols (L1, L2 and L3 as described in Table 1), based on our previous experience with antimicrobial blue laser irradiation [16]. Bacterial growth after 24 hours was evaluated by measuring the OD 600 and compared with nontreated bacteria (CTRL).…”
Section: Methodsmentioning
confidence: 99%
“…In vivo studies in mouse burns showed that blue-light exposure could drastically reduce bacterial load and effectively protect mice from lethal infection with P. aeruginosa [ 312 ]. Blue light presumably exerts its effect on bacterial cells by exciting porphyrins which then generate ROS, as suggested by the resistance to blue light exhibited by a P. aeruginosa mutant defective in porphyrin biosynthetis [ 313 ]. Additionally, ultraviolet C light has been shown to efficiently eradicate Pseudomonas biofilms on precontaminated catheter-like tubes [ 314 ].…”
Section: Control Of Biofilm Infectionsmentioning
confidence: 99%
“…However, although we obtained superior and sustained eradication following the dual-treatment protocol, dark toxicity of the PS toward S. pneumoniae became evident, consistent with previous reports describing a bactericidal effect of PSs alone, in the absence of illumination, toward Gram-positive organisms due to a more rapid intracellular drug accumulation ( 29 , 31 33 ). Likewise, the observed antimicrobial effect of light exposure alone has been demonstrated in multiple bacterial species, with Gram-negative bacteria often showing increased sensitivity to photoinactivation, which has been attributed to the presence of endogenously synthesized cellular porphyrins that act as native PSs and, upon light activation, cause lethal ROS production ( 21 , 32 , 34 , 35 ). Thus, our data suggest the application of aPDT is an effective antimicrobial strategy that both interferes with maintenance of bacterial viability and disorganizes and compromises the integrity of the biofilm structure.…”
Section: Discussionmentioning
confidence: 99%